Amphipathic monolith-supported palladium catalysts for chemoselective hydrogenation and cross-coupling reactions. Issue 4 (12th January 2017) - Monguchi, Yasunari; Wakayama, Fumika; Ueda, Shun; Ito, Ryo; Takada, Hitoshi; Inoue, Hiroshi; Nakamura, Akira; Sawama, Yoshinari; Sajiki, Hironao
Abstract : Monolithic polymer-supported, effective, and reusable palladium catalysts were developed for cross-coupling reactions and hydrogenation. Abstract : A palladium catalyst immobilized on an amphipathic and monolithic polystyrene–divinylbenzene polymer bearing strongly acidic cation exchange functions (sulfonic acid moieties) (Pd/CM) was developed. It was used as a catalyst for hydrogenation and ligand-free cross-coupling reactions, such as the Suzuki–Miyaura, Mizoroki–Heck, and copper- and amine-free Sonogashira-type reactions, together with a palladium catalyst supported on monolithic polymer (Pd/AM) bearing basic anion exchange functions (ammonium salt moieties), which has been in practical use for the decomposition of hydrogen peroxide produced as a byproduct during the manufacture of ultrapure water. While the Pd/CM was highly active as a catalyst for the hydrogenation and a variety of reducible functional groups could be reduced, the use of Pd/AM led to a unique chemoselective hydrogenation. Aromatic carbonyl groups were tolerant under the Pd/AM-catalyzed hydrogenation conditions, although benzyl esters, benzyl ethers, and N -Cbz groups could be smoothly hydrocracked. The cross-coupling reactions readily proceeded using either catalyst. The palladium leaching from the Pd/CM into the reaction media was never observed during the Sonogashira-type reaction, which was hardly achieved by other palladium-supported heterogeneous catalysts due to the good affinity of the palladium species with alkynes.